WORKING ENVIRONMENT AND JOB SATISFACTION AMONG HEALTH PROFESSIONAL WORKING AT A TERTIARY CARE HOSPITAL OF PAKISTAN - Aziz, Imrana; Kumar, Ramesh; Rathore, Anita; Lal, Manohr (Journal of Ayub Medical College Abbottabad, 2015)
Background: Work environment is believed to be a major factor for better performance of human resource for health in any organization. This study concentrated on multiple factors involved in job satisfaction was appraised to critique their efficient significance in calculation of the health professional liking. Factors included job matched with workers' skills/experience, incentives, supervision, administrator support; convenient work load, training, appreciation, low pay and job protection were major contributors in job satisfaction. Methods: A mix method study was done in 2014; an initial descriptive cross sectional survey was done followed by qualitative approach. Eighteen in-depth interviews with health care providers were conducted after taking written consent. Nodes, sub-nodes and final themes were generated during qualitative data analysis. Results: Main findings and themes were generated after making the nodes and sub-nodes from the most frequent responses. These themes were; absence of work pressure, work place safety, social support, learning opportunities, and employee influence on conditions and recognition individual or team efforts. Conclusion: Work environment is a major contributing factor towards job satisfaction among the health workers. Keywords: Work environment, job satisfaction, health workers and human resources